2017
DOI: 10.1186/s13741-017-0063-6
|View full text |Cite|
|
Sign up to set email alerts
|

American Society for Enhanced Recovery (ASER) and Perioperative Quality Initiative (POQI) Joint Consensus Statement on Optimal Analgesia within an Enhanced Recovery Pathway for Colorectal Surgery: Part 2—From PACU to the Transition Home

Abstract: BackgroundWithin an enhanced recovery pathway (ERP), the approach to treating pain should be multifaceted and the goal should be to deliver “optimal analgesia”, which we define in this paper as a technique that optimizes patient comfort and facilitates functional recovery with the fewest medication side effects.MethodsWith input from a multidisciplinary, international group of experts and through a structured review of the literature and use of a modified Delphi method, we achieved consensus surrounding the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…7 Early oral intake in the immediate postoperative period allows optimization of multimodal pain regimens that include oral non-opioid pain medications, thereby minimizing the need for opioid analgesia. 25,26 Prior studies have shown shorter hospital LOS for MIS compared to open colorectal surgery, and shorter LOS for RS compared to LS groups. 27e30 The shorter LOS for MIS compared to open groups, and RS compared to LS groups, is likely multifactorial, but less parenteral opioids and quicker postoperative transition to oral intake result in earlier return of gastrointestinal activity, less ileus, and earlier discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Early oral intake in the immediate postoperative period allows optimization of multimodal pain regimens that include oral non-opioid pain medications, thereby minimizing the need for opioid analgesia. 25,26 Prior studies have shown shorter hospital LOS for MIS compared to open colorectal surgery, and shorter LOS for RS compared to LS groups. 27e30 The shorter LOS for MIS compared to open groups, and RS compared to LS groups, is likely multifactorial, but less parenteral opioids and quicker postoperative transition to oral intake result in earlier return of gastrointestinal activity, less ileus, and earlier discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Varying protocols may include elements such as acetaminophen, nonsteroidal anti-inflammatory medications, gabapentin, transversus abdominis plane blocks, and intrathecal or epidural analgesia options. 35 The PHD dataset does not identify which institutions had established enhanced recovery pathways with multimodal pain management strategies 25,26 and so the impact of these pathways on decreasing or obviating inpatient opioid use could not be determined in our study. 25,26 However, we implemented a multilevel random-effects regression model to control for hospital-level clustering of opioid prescribing patterns and the results support less inpatient opioid use in MIS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After publication of this article (Scott et al 2017 ), it was noticed that the HTML version contained technical errors regarding the collaborator information of the Perioperative Quality Initiative (POQI) I Workgroup. The Declarations section was missing the acknowledgements for the group.…”
Section: Correctionmentioning
confidence: 99%
“…They have driven advancements in intravenous fluid therapy and transformed the landscape of clinical practice through the success of enhanced recovery after surgery (ERAS) programmes. It has been proposed that a rational assessment tool for ERAS would be a succinct patient-related outcome measure, such as whether or not the patient is 'DREAMing' within 24 h of surgery (Drinking, EAting, and Mobilising), 37 a concept recently upgraded to 'DREAMS' 38 by the addition of 'Sleep'. It is an interesting observation that all of these components also happen to be the most important Zeitgebers, and therefore contribute to the preservation of a healthy circadian rhythm.…”
mentioning
confidence: 99%